2010
DOI: 10.1001/archneurol.2010.249
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy and Lobar Intracerebral Hemorrhage

Abstract: Background:The vascular pathogenesis underlying lobar intracerebral hemorrhage (ICH) is unclear.Objective: To determine whether certain retinal microvascular signs are associated with lobar ICH to improve understanding of its underlying cerebral vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…39 Furthermore, retinal micro-vascular abnormalities are known to reflect arteriolar damage from hypertension and other processes 11 and are consistently related with stroke, cerebral atrophy and stroke-related death. 1420 As such, retinal micro-vascular abnormalities are hypothesized markers of generalized vascular disease. As with previous reports, 40 we showed that narrower retinal arteriolar caliber was correlated with increased SBP and DBP, and self-reported diagnosis of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Furthermore, retinal micro-vascular abnormalities are known to reflect arteriolar damage from hypertension and other processes 11 and are consistently related with stroke, cerebral atrophy and stroke-related death. 1420 As such, retinal micro-vascular abnormalities are hypothesized markers of generalized vascular disease. As with previous reports, 40 we showed that narrower retinal arteriolar caliber was correlated with increased SBP and DBP, and self-reported diagnosis of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the retinal vasculature 10,11,13 may be markers of concomitant cerebral microvascular disease, and are closely related to hypertension, stroke, MRI-detected subclinical infarcts and white matter lesions, cerebral atrophy and stroke-related death. 1420 …”
Section: Introductionmentioning
confidence: 99%
“…(34) Retinal micro-aneurysms, hemorrhages and cotton wool spots were associated with lobar ICH as opposed to deep ICH or cerebral infarct in non-diabetics. (35) The authors proposed that the differences in arteriolar wall findings, namely AV nicking and arteriolar narrowing, in the retina of patients with deep ICH, versus retinal microaneurysms, hemorrhages and cotton wool spots in lobar ICH and cerebral infarct reflect the different cerebral vascular pathologies that underlie these distinct cerebral vascular events.…”
Section: Relationship Between Chronic Retinal Microvascular Disease Amentioning
confidence: 99%
“…Because the retinal vasculature is easily accessible in vivo using retinal imaging, there is an increasing interest to use the retina as model to study pathologic changes in the cerebral vasculature. Retinal signs that have been associated with intracerebral hemorrhage include retinal vessel calibres, signs of age-related macular disease, retinopathy, focal narrowing of arterioles, and arteriovenous nicking [4648]. However, many of these signs are not specific for intracerebral hemorrhage and have also been associated with ischemic stroke and its subtypes.…”
Section: Pre-clinical Imaging Markersmentioning
confidence: 99%